Virtual Communities of Collaborative Learning for Higher Education - Sotomayor, Gilda E. (2014)
This article aims to outline and project three new learning scenarios for Higher Education that, after the emergence of ICT and communication through the Network-lnternet, have come under the generic name of virtual communities. To that end, we start from a previous conceptual analysis on collaborative learning, cooperative learning and related concepts taking place in these communities and serving as a basis for sorting them into three types in particular: communities of educational work of professional practice and scientific knowledge. Virtual communities where the activities undertaken and skills acquired are set as important parts of our personal learning development, wich are necessary to build the Knowledge Society.